Assessment of human exposure to electric and magnetic fields near transmission lines using FEMM - Glushica, Bojan (JET on-line, 2023)
The intensity of ELF electric and magnetic fields near transmission lines is of particular interest in environmental and equipment protection studies. The use of numerical tools is the most efficient method for their assessment. In this paper, we numerically compute the electric and magnetic fields near different configurations of high-voltage transmission lines using the open- source software FEMM 4.2. Computed fields are compared with reference levels related to human exposure to electromagnetic fields. The accuracy of the applied method is validated with published, numerically computed and measured results.
Keywords: daljnovodi; electric field; electromagnetic computation; električno polje; elektromagnetno računanje; finite elements method; magnetic field; magnetno polje; metoda končnih elementov; transmission lines